High fire temperature changes soil aggregate stability in slash-and-burn agricultural systems - Thomaz, Edivaldo Lopes (2017)
Fire is a key controlling factor in ecosystem dynamics worldwide, especially, in tropical areas under slash-and-burn agricultural systems. Farmers use fire as a tool to clean the land, and benefit from nutrient enrichment from ash-soil heating. However, fire can cause some detrimental effects on soil systems, such as organic carbon depletion, increased soil erodibility, and changes to aggregate stability. In this study, an experimental fire was applied to a plot of land following the local traditional practice of slash-and-burn. The fire temperature was monitored in the field, and its effect on soil aggregate stability was assessed. The fire temperature on soil surface was measured in four trenches, and it ranged from 355 to 660 °C (average 484 ± 142 °C). The fire temperature did not affect soil organic matter content. However, aggregate stability increased by 10 % in comparison to unburned soil. Moreover, the geometric mean diameter of burned soil was 20 % higher than that of unburned soil. In conclusion, high fire temperature changes soil aggregate stability in slash-and-burn agricultural systems.